Uma casa, nossa história: perspectivas sociomuseólogicas e de educação patrimonial para o Museu Pedro Ludovico - Fernandes, Vanessa Cláudio (2022)
This research aims, from the perspective of Sociomuseology in line with methodological approach with Heritage Education, associating museums, education and heritage. It is from of this relationship, considering the approaches of the New Museology, to use the Pedro Ludovico house museum as an object. The entire study exposed here is governed by the intention of producing a Thematic notebook that conceives the Pedro Ludovico Museum, in Goiânia-GO, heritage state, far beyond its buildings and objects, but from the social function that must exercise from the perspective of Sociomuseology. Considering aspects of collective memory and cultural of those involved in the workshops that will be proposed in the Thematic Notebook, in order to within the proposed examples, protagonists in the field of heritage, in this case, specifically, heritage of the city. Finally, we will propose a museological current that conceive the Pedro Ludovico Museum far beyond its buildings and objects, but from the social function, which it must exercise in the category of non-formal education. All proposals will be worked within methodological aspects of Heritage Education from the perspective Freirean dialogic. It is expected that the teaching proposals presented will contribute to a challenging education, capable of promoting didactic situations that allow the questioning institutionalized cultural goods, allowing subjects to get to know each other and realize how memory and heritage are both fields of tensions and conflicts fields of identity construction and social formation. That's why they need to be viewed critically. by the awareness of its own history, whether peripheral or not, minority or not, making This way, it is possible to demystify the heritage, emphasizing that it is the result of choices that need to be be questioned and resignified to exercise their social function.